RESEARCH BASED LEARNING DALAM MENINGKATKAN CREATIVE THINKING SKILLS SISWA : SEKOLAH DASAR NEGERI TAMANAN 1 BONDOWOSO - SUCIK IKE WAHYUNI (Dewan Pendidikan Bondowoso, 2020)
This study aims to improve students' creative thinking skills through research-based learning. This study uses a quantitative approach. The sample consisted of two classes, namely the control class with 31 students and the experimental class with 30 students. The results of this study indicate that there is a significant difference in sig (2-tailed) values ​​between the control class and the experimental class. It can be ignored that the application of a research-based learning model can improve the creative thinking skills of elementary school students. Thus, it is important to carry out further research related to this theme.